Severe skeletal toxicity from protracted etidronate therapy for generalized arterial calcification of infancy1. (15th January 2013) - Otero, Jesse E; Gottesman, Gary S; McAlister, William H; Mumm, Steven; Madson, Katherine L; Kiffer‐Moreira, Tina; Sheen, Campbell; Millán, José Luis; Ericson, Karen L; Whyte, Michael P
Abstract Generalized arterial calcification (AC) of infancy (GACI) is an autosomal recessive disorder that features hydroxyapatite deposition within arterial elastic fibers. Untreated, approximately 85% of GACI patients die by 6 months of age from cardiac ischemia and congestive heart failure. The first‐generation bisphosphonate etidronate (EHDP; ethane‐1‐hydroxy‐1, 1‐diphosphonic acid, also known as 1‐hydroxyethylidene‐bisphosphonate) inhibits bone resorption and can mimic endogenous inorganic pyrophosphate by blocking mineralization. With EHDP therapy for GACI, AC may resolve without recurrence upon treatment cessation. Skeletal disease is not an early characteristic of GACI, but rickets can appear from acquired hypophosphatemia or prolonged EHDP therapy. We report a 7‐year‐old boy with GACI referred for profound, acquired, skeletal disease. AC was gone after 5 months of EHDP therapy during infancy, but GACI‐related joint calcifications progressed. He was receiving EHDP, 200 mg/day orally, and had odynodysphagia, diffuse opioid‐controlled pain, plagiocephaly, facial dysmorphism, joint calcifications, contractures, and was wheelchair bound. Biochemical parameters of mineral homeostasis were essentially normal. Serum osteocalcin was low and the brain isoform of creatine kinase and tartrate‐resistant acid phosphatase 5b (TRAP‐5b) were elevated as in osteopetrosis. Skeletal radiographic findings resembled pediatric hypophosphatasia with pancranial synostosis, long‐bone bowing, widened physes, as well as metaphyseal osteosclerosis, cupping and fraying, and "tongues" of radiolucency. Radiographic features of osteopetrosis included osteosclerosis and femoral Erlenmeyer flask deformity. After stopping EHDP, he improved rapidly, including remarkable skeletal healing and decreased joint calcifications. Profound, but rapidly reversible, inhibition of skeletal mineralization with paradoxical calcifications near joints can occur in GACI from protracted EHDP therapy. Although EHDP treatment is lifesaving in GACI, surveillance for toxicity is crucial. © 2013 American Society for Bone and Mineral Research